FRENCH â€œFIDUCIEâ€ AND RUSSIAN â€œÐ”ÐžÐ’Ð•Ð Ð˜Ð¢Ð•Ð›Ð¬ÐÐžÐ• Ð£ÐŸÐ ÐÐ’Ð›Ð•ÐÐ˜Ð• Ð˜ÐœÐ£Ð©Ð•Ð¡Ð¢Ð’ÐžÐœâ€ (TERMINOLOGICAL PECULIARITIES) - Gvelesiani, Irina (European Scientific Journal, ESJ, 2014)
â€œTrustâ€ is â€œthe greatest and most distinctive achievement performed by Englishmen in the field of jurisprudenceâ€. This universal institution appeared in the Medieval English law and has become very popular during the last decades. Different variations of a trust mechanism have emerged in some world countries. The given paper tries to answer the demands of the modern epoch via making a precise description of the French and Russian trust-like devices. It makes an in-depth analysis, singles out major terminological units and underlines the fact, that the newly-established French and Russian mechanisms have to undergo several stages for turning into faithful reflections of the Anglo-American model of â€œtrustâ€.